2010
DOI: 10.1044/0161-1461(2009/08-0077)
|View full text |Cite
|
Sign up to set email alerts
|

Index of Productive Syntax for Children Who Speak African American English

Abstract: Purpose The validity of the Index of Productive Syntax (IPSyn; Scarborough, 1990) for children who speak African American English (AAE) was evaluated by conducting an item analysis and a comparison of the children’s scores as a function of their maternal education level, nonmainstream dialect density, age, and clinical status. Method The data were language samples from 62 children; 52 of the children were between the ages of 4 and 6 years and were classified as developing typically, and 10 were 6 years old w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 42 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…In addition, the IPSyn itself may have limits to the range of interpretation. For example, Oetting et al (2010) reported that the developmental changes in IPSyn plateau after the age of 4 years in children without intellectual disability. Future research needs to better examine the sensitivity of the index with older individuals whose language may be similar to younger children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the IPSyn itself may have limits to the range of interpretation. For example, Oetting et al (2010) reported that the developmental changes in IPSyn plateau after the age of 4 years in children without intellectual disability. Future research needs to better examine the sensitivity of the index with older individuals whose language may be similar to younger children.…”
Section: Discussionmentioning
confidence: 99%
“…The index was originally developed for children between the ages of 24 and 48 months, although it has been used beyond that age range (Hewitt et al, 2005;Oetting et al, 2010;Rescorla & Turner, 2015). The usefulness of the IPSyn as a measure of expressive syntactic abilities in TD children and various clinical populations has been shown in several studies (Price et al, 2008;Rescorla et al, 2000;Rescorla & Turner, 2015;Roberts et al, 2007;Scarborough et al, 1991).…”
Section: Measures Of Expressive Syntaxmentioning
confidence: 99%
“…Although the IPSyn (Scarborough, 1990) appears to have limited diagnostic value for 6-year-olds, who are older than the age range for which it was designed (Oetting et al, 2010), we included the Sentence Structure subscale to help confirm that our protocol was successful in eliciting a broad range of syntactic forms.…”
Section: Coding the Ls Measuresmentioning
confidence: 99%
“…As Green (2011) noted, quantitative features-based approaches, although limited in their ability to describe qualitative aspects of NMAE, have been useful for diagnostic purposes of verifying participant use of certain NMAE forms that may, because of differences in morphosyntax, overidentify children as having a language impairment (e.g., Oetting et al, 2009;Seymour, Bland-Stewart, & Green, 1998;Stockman, Guillory, Siebert, & Bolt, 2013), and for examining typical and atypical language behaviors in different subgroups of NMAE speakers (e.g., Apel & Thomas-Tate, 2009;Horton-Ikard, 2010;Oetting & Garrity, 2006). In addition, each of the above measures have been used fairly recently for empirical investigations concerned with the following three areas: (a) quantifying spoken production of NMAE, (b) determining whether style shifting (movement from NMAE to Mainstream American English [MAE]) is occurring in the spoken language production of children as they grow older or perform different tasks, and (c) understanding the relationship between spoken NMAE and literacy outcomes (e.g., Champion, Rosa-Lugo, Rivers, & McCabe, 2010;Terry, Connor, Petscher, & Conlin, 2012;Thompson, Craig, & Washington, 2004).…”
mentioning
confidence: 98%